MODEL PENGEMBANGAN KINERJA DOSEN SWASTA (Studi pada Karyawan yang berprofesi sebagai Dosen) - RAHMAN, FATKHURAHMAN; SUROTO, BAMBANG (Human Sustainability Procedia, 2018)
The problem of the performance of private lecturers when associated with the level of attendance becomes a phenomenon. This phenomenon leads to some private lecturers in working to become faculty at college into a side job so that work time on campus and come apart for teaching to be very limited. To the campus just for the sake of teaching alone and finished teaching straight home or go home straight home, to be a question whether with such a presence makes private lecturers have low performance. Through survey research to 32 permanent lecturers at economic collage in Pekanbaru through questionnaires distributed online and analyzed using SEM WarpPLS. The results showed that the intensity of the presence of private lecturers had a negative andsignificant influence on their performance.